2007
DOI: 10.1093/occmed/kqm041
|View full text |Cite
|
Sign up to set email alerts
|

Peer responses to perceived stress in the Royal Navy

Abstract: The results are generally encouraging; the majority of those interviewed would actively involve themselves in the care of their peers and refer them on appropriately if the situation deteriorated. Most individuals interviewed saw DSH as a real, predominately medical problem that required immediate active intervention. However, many felt that help seeking could be detrimental to one's career within the services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, thinking less of a team member receiving mental health treatment was the least frequently endorsed stigma item at both time points. Previous research suggests that this finding may not be confined to the current research; Royal Navy personnel reportedly felt confident that they could support distressed personnel, including those that talk about self-harm (Greenberg et al, 2007). This suggests that leaders are being effective in fostering cohesion, however, for the small number of personnel who felt that they could not spot colleagues who were distressed nor talk about thoughts and feelings, improving unit cohesion may be an important potential target for intervention by commanders.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, thinking less of a team member receiving mental health treatment was the least frequently endorsed stigma item at both time points. Previous research suggests that this finding may not be confined to the current research; Royal Navy personnel reportedly felt confident that they could support distressed personnel, including those that talk about self-harm (Greenberg et al, 2007). This suggests that leaders are being effective in fostering cohesion, however, for the small number of personnel who felt that they could not spot colleagues who were distressed nor talk about thoughts and feelings, improving unit cohesion may be an important potential target for intervention by commanders.…”
Section: Discussionmentioning
confidence: 72%
“…These data are important for health service planners, providers and policy makers. Routinely collected data based on presentation to health care providers is problematic, since many are reluctant to disclose mental disorders within the military environment [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, male students were less willing to help and more likely to view those who engage in NSSI as being manipulative (Law et al, 2009). In their study, Greenberg, Henderson, Langston, Iversen, and Wessely (2007) examined how trained military personnel would react when a colleague expressed desires to engage in NSSI. While most reported that they would either make a management or medial referral, a small portion of the junior ratings (7%) reported that they would have a ‘negative reactions’.…”
Section: Resultsmentioning
confidence: 99%